2012
DOI: 10.1136/bmj.e5027
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and cognitive decline among women: prospective cohort study

Abstract: Objective To evaluate the association between migraine and cognitive decline among women.Design Prospective cohort study. Setting Women's Health Study, United States.Participants 6349 women aged 65 or older enrolled in the Women's Health Study who provided information about migraine status at baseline and participated in cognitive testing during follow-up. Participants were classified into four groups: no history of migraine, migraine with aura, migraine without aura, and past history of migraine (reports of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 37 publications
5
50
1
6
Order By: Relevance
“…Some studies have shown no significant differences among those with and without migraine [11,12,13], whereas others have shown worse cognitive function among those with prior migraine [14,15,16]. A prospective cohort study of 6,354 women aged 65 years and older who experience migraines showed that they exhibit more cognitive decline in later years than women with no history of migraine [17]. However, the incidence of dementia increases with age in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown no significant differences among those with and without migraine [11,12,13], whereas others have shown worse cognitive function among those with prior migraine [14,15,16]. A prospective cohort study of 6,354 women aged 65 years and older who experience migraines showed that they exhibit more cognitive decline in later years than women with no history of migraine [17]. However, the incidence of dementia increases with age in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Four longitudinal studies have been performed that assess the association between migraine and cognitive decline in adults (see Table 1) using data from the Maastricht Aging Study (MAAS), 24 the Baltimore Epidemiologic Catchment Area Study (ECA), 25 the Epidemiology of Vascular Ageing Study (EVA) 26 and the Women’s Health Study (WHS). 27 Unlike some of the cross-sectional studies, all of the longitudinal studies have used population-based samples.…”
Section: Longitudinal Studiesmentioning
confidence: 99%
“…2527 The remaining study only asked participants whether a doctor had diagnosed them as having migraine headaches. 24 Three studies assessed whether their participants experienced migraine with aura.…”
Section: Longitudinal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies showed that migraine and CH patients have a decline of memory processing during headache attack, but not between attacks and no progressive cognitive decline was detected [145,146]. While our results are solely structural in nature, given the strong coupling between structure and function in the brain, functional correlates also have to be considered.…”
Section: Cluster Headachementioning
confidence: 90%